Design Analysis of CIMB Bank's Website - Aziz, MRA; Mohammad Noorizzuddin Nooh (Penerbit Utm Press, 2024)
Islamic banking has emerged in recent decades as one of the most important trends in the financial world, side by side with conventional banking. Website design has become a very powerful tool in disseminating information of a particular banking institution and this phenomenon has been fully utilized by both conventional and Islamic banks throughout the world. The purpose of this article is to analyze website design of CIMB Bank that offers both conventional and Islamic financing facilities. The methodology employed in this article is qualitative in nature through examining the websites of CIMB Bank. The finding shows that CIMB Bank needs to improve their both website designs in order to attract more customers to their websites and give true information with regard of their products and services. It is further suggested that future researcher tries to explore more in-depth website designs in terms of products and services provided by the conventional and Islamic banking institutions in order to increase their market shares.